Dung-applied anthelmintic drug moxidectin alters free-living soil nematode communities - Milkereit, Janina (2026)
Moxidectin (MOX) belongs to the macrocyclic lactones, a class of anthelmintic drugs widely used in livestock that can enter the soil environment and persist by binding to soil organic matter. While MOX is effective against gastrointestinal parasitic nematodes, its potential impact on free-living soil nematodes remains largely unexplored. In a controlled 8-week pot experiment, we examined how MOX, applied via sheep dung, affects free-living soil nematode communities and related ecological indices of soil condition. The effects of increasing MOX dosages (0.25, 0.5 and 1 mg/pot) on nematode abundance, diversity and trophic structure were investigated and microbial biomass carbon (MBC) and soil nitrogen (N) were assessed. While total nematode numbers remained unchanged, MOX significantly altered the nematode community composition, with a decline in nematodes classified as c-p3 to c-p5 (on the colonizer-persister scale), typically associated with stable soil conditions. Further, MOX reduced key ecological indices, such as the Maturity Index (MI2–5) and Structure Index (SI), indicating increased environmental stress and reduced food web complexity. Low and medium MOX treatments further reduced Shannon diversity and nematode community evenness. Opportunistic c-p1 nematodes were related to increases in MBC whereas c-p2 nematodes negatively correlated with MBC. However, MBC was not affected by MOX. While mineral N was not affected by MOX, we found that total N was reduced in soils, suggesting changes in soil N mineralization. Our findings highlight the need for qualitative research on the ecological consequences of veterinary pharmaceuticals in soil ecosystems, and their potential long-term effects on soil biodiversity and functionality.